Local authority initiative in promoting sustainable community livelihood in urban areas - Abdullah, Yusfida Ayu; Yakob, Hamizah; Mohd Nor, Marina; Ahmad Karim, Nur Amalina; Marzukhi, Marlyana Azyyati (Journal of Islamic, Social, Economics and Development, 2025)
Urban areas are often regarded as places with many economic opportunities, services, infrastructure and facilities. However, the cities also embrace many challenges and pose threats to the urban population. Urban community in big cities in Malaysia like Shah Alam faces issues like urban poverty, health problems, inequality, disability rights, crime and many others. This paper presents the outcome of a study that led to creating an action plan for the Shah Alam, Malaysia community. The study's objective is to systematically undergo a process that infuses the community's needs and aspirations, therefore enabling the formulation of an action plan that promotes sustainable community livelihood in an urban area. The method used a qualitative approach, using the case study technique. Shah Alam's communities were engaged in three Focus Group Discussion sessions involving community representatives, stakeholders, and various agencies in community development. A total of 339 were selected through Purposive Sampling. Site Observations were conducted to examine the lifestyle of Shah Alam's communities. Results demonstrated that the communities were looking forward to a strategic action plan by the local authority to improve their livelihood. The end product is an action plan that will become a primary reference for the city council in promoting sustainable community livelihood in Shah Alam.